Harnessing Endogenous Cellular Mechanisms for Bone Repair - Lo Sicco, Claudia; Tasso, Roberta (Frontiers in Bioengineering and Biotechnology, 2017)
Although autologous tissue transplantation represents a valid approach for bone repair, it has encountered crucial barriers in therapeutic translation, not least the invasive process necessary for stem cell isolation. In recent years, the scientific community has made significant strides for identifying new treatment options, and great emphasis has been placed on the tight interaction between skeletal and immune system in modulating the outcome of bone repair. Within the context of specific injury environmental cues, the cross-talk among inflammatory cells and tissue resident and/or circulating progenitor cells is crucial to finely coordinate repair and remodeling processes. The appropriate modulation of the inflammatory response can now be considered a new trend in the field of regenerative medicine, as it raises the attracting possibility to enhance endogenous progenitor cell functions, finally leading to tissue repair. Therefore new treatment options have been developed considering the wide spectrum of bone-inflammation interplay, considering in particular the cell intrinsic cues responsible for the modulation of the injured environment. In this review, we will provide a panoramic overview focusing on novel findings developed to uphold endogenous bone repair.